2021
DOI: 10.1108/idd-09-2020-0113
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting perception of Indian adolescent students toward interactive online mental health information during COVID-19

Abstract: Purpose This study aims to identify the critical factors affecting the perception of adolescent students toward interactive online mental health information available on health-related websites. Design/methodology/approach The primary data was collected with the help of an online self–structured questionnaire. The questionnaire includes the identified variables extracted from previous literature related to the mental health information websites using the Likert scale. The respondents include the adolescent s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 74 publications
0
0
0
Order By: Relevance
“…The findings of the present study support these arguments as SMCs give rise to negative emotions which result in inferiority complex, thus, hampering the well-being of the users. The studies have also found that individuals who spend more time on social networking sites tend to compare themselves with others and perceive that others are leading a successful, healthy and better life than them (Bhat and Gupta, 2019; Suls and Wheeler, 2013; Kaushal and Dogra, 2022). Social media can exacerbate the tendency for SMC by providing a platform for constant comparisons to others, often leading to feelings of inadequacy and low self-esteem (de Vries et al , 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the present study support these arguments as SMCs give rise to negative emotions which result in inferiority complex, thus, hampering the well-being of the users. The studies have also found that individuals who spend more time on social networking sites tend to compare themselves with others and perceive that others are leading a successful, healthy and better life than them (Bhat and Gupta, 2019; Suls and Wheeler, 2013; Kaushal and Dogra, 2022). Social media can exacerbate the tendency for SMC by providing a platform for constant comparisons to others, often leading to feelings of inadequacy and low self-esteem (de Vries et al , 2018).…”
Section: Discussionmentioning
confidence: 99%